LIBERAL FEMINISM PORTRAYED IN DIALOG ON THE MAIN CHARACTER OF CINDERELLA 2021 MOVIE - I Gede Agus Eka Palguna (IKIP Siliwangi, 2023)
This paper discussed feminism in Cinderella 2021 movie directed by Kay Cannon in 2021. This movie is adapted from Charles Perrault’s fairy tale which was written in 1697. The aim of this research is to analyze how feminism is described by the main character. The other objective is to find out the example of liberal feminism on the main character based to Tong’s theory. The researcher used descriptive qualitative methods which analyzed the content of the movie. All data is presented in the form of words, and sentences are also used in library research to collect data by reading and selecting quotations from the Cinderella 2021 movie. As the result of the study, liberal feminism that described through the main character are shown when Ella against the inequality that happens to her. And shown through the dialogue, body language, voice tone, as well as choice of word. Keywords: Feminism; Cinderella 2021; Liberal Feminism